Use of Robotics in Medical Rehabilitation: A Systematic Analysis of the Literature on Clinical Effectiveness and Implementation - Putri Amel (Science and Applied Journal (SIAP), 2024)
The utilization of robotics in medical rehabilitation has emerged as a promising approach to enhance the effectiveness of rehabilitation interventions. This systematic literature review provides an in-depth analysis of the effectiveness and clinical implementation of robotic technology in medical rehabilitation. Through a comprehensive literature review, various robotic systems and technologies utilized in medical rehabilitation are identified and evaluated. Comparative analysis of empirical evidence from clinical studies reveals the efficacy of robotics in improving patient outcomes across different domains of rehabilitation. Furthermore, the discussion encompasses the challenges and opportunities associated with the clinical implementation of robotic technology in rehabilitation practice. Future directions and advancements in robotic rehabilitation are explored, highlighting the potential for technological innovations to further enhance the quality and accessibility of rehabilitation services. This review contributes to a deeper understanding of the role of robotics in medical rehabilitation and provides insights for clinical practice and research.